Dinâmica Socioprodutiva de Territórios Susceptíveis à Desertificação no Estado da Bahia: o caso de Irecê - Macêdo, Luiz Rogério de Lima (2011)
The Desertification has mobilized the interest of researchers and international agencies and Brazilian since 1970. This interest won strength from the last decade of the twentieth century, when several countries linked to United Nations Organization, among which Brazil, decided to ratify the UN Convention to Combat Desertification. In Brazil, the Brazilian Semiarid Territory, historically known for the dry matter, was demarcated as susceptible to the phenomenon. The meanings more immediate of these events were the construction of the National Plan for Combating Desertification and Mitigating the Effects of Dry (PAN-Brazil), adherence to the theme of many researchers, and determination for the States included in the areas likely to draw up plans and specific policies. In the State of Bahia, which owns a significant portion of its territory under these conditions, the situation is no different. The objective defined for this thesis was to identify and analyze the occurrence of sub-regional patterns in the Territory of Identity Irecê, located in the semiarid region of Bahia, from social and economic indicators, using qualitative and quantitative methods. Among the issues addressed bindings stand out among the processes of degradation and desertification with the patterns of uneven territorial development, associated with the policies of modernization of the agricultural sector in ways that conservatives marked the Northeast Semiarid and, within that, the Territory of Identity Irecê. It was noted that this regional space degradation and desertification are related to the legacy of economic growth model based on the notion of inexhaustible natural resources. The territorial patterns resulting from regional development process confirm the sub-region of the Plateau Irecê as the privileged area for investment. And while state subsidies that were aimed at the sub-region, the living conditions of the municipalities that make up remained the same or worse to those who did not enjoy such investments.